Manajemen Pengembangan Ekonomi Kreatif Santri Di Pondok Pesantren Miftahul Ulum Banyuayu Pamoroh Kadur Pamekasan - hafid efendy; Siti Anisyah (State Islamic Institute of Madura, 2019)
This research was motivated by the researchers' interest in developing the interests and creative economic talents of the santri at the Pamoroh Kadur Pamekasan Islamic Boarding School in Miftahul Ulum Banyuayu. The results of the study showed that the management of the development of the santri's creative interests and economic talents was: first, it was still directly controlled by the caregivers who planned and managed the management as caregivers. Second, the creative economic management system of the santri uses a manual system for archiving, and the TOT system or regeneration / cadre to develop the interests and talents. Third, as for the driving factor, human resources are capable and able to work as well as adequate natural resources, as well as direct motivation given by caregivers, while the inhibiting factors are lack of time and limitations in making crafts because they use human labor, also because students experience fatigue due to following Islamic boarding school activities so that students become lazy. Fourth, the solution of the management inhibiting factors in developing the interest and creative talents of santri is to carry out several evaluations at the beginning and end of the year.